2020
DOI: 10.1111/jir.12778
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the initial response to COVID‐19 on long‐term care for people with intellectual disability: an interrupted time series analysis of incident reports

Abstract: Background The lockdown-measures in response to COVID-19 taken by long-term care organisations might have impacted problem behaviour and behavioural functioning of people with intellectual disability. This study tested changes in reported incidents, in particular regarding aggression, unexplained absence and, for contrast, medication errors. Methods Metadata on weekly incident and near-incident reports from 2016 to June 2020 involving over 14 000 clients with mild to serious intellectual disability of 's Heere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 18 publications
3
52
0
4
Order By: Relevance
“…The left column describes the main categories in this group of articles. Subcategory Country and references Effects on spreading Argentina, Bolivia, Brazil, Chile, Colombia, Paraguay, Peru, and Uruguay [309] ; Australia [310] Bangladesh [311] ; China [31] , [32] , [33] , [312] , [313] , [314] , [315] ; China, Germany, India, Italy, Singapore, South Korea, Spain, UK, USA [316] ; Italy [317] , [318] ; New Zealand [319] ; Puerto Rico [320] ; South Korea [321] ; Taiwan [322] ; USA [323] , [324] , [325] , [326] , [327] , [328] ; 44 countries [329] ; 53 countries [330] ; 56 countries [331] ; 142 countries [332] ; 149 countries [333] Effects on behaviors China [334] ; China, Italy [335] ; Denmark, Sweden [336] ; Germany [337] USA [338] , [339] , [340] , [341] ; 20 countries [342] ; 67 countries [343] Effects on medical practice Italy [344] ; Netherlands [345] ; UK [346] …”
Section: Quantifying the Effects On Npismentioning
confidence: 99%
See 1 more Smart Citation
“…The left column describes the main categories in this group of articles. Subcategory Country and references Effects on spreading Argentina, Bolivia, Brazil, Chile, Colombia, Paraguay, Peru, and Uruguay [309] ; Australia [310] Bangladesh [311] ; China [31] , [32] , [33] , [312] , [313] , [314] , [315] ; China, Germany, India, Italy, Singapore, South Korea, Spain, UK, USA [316] ; Italy [317] , [318] ; New Zealand [319] ; Puerto Rico [320] ; South Korea [321] ; Taiwan [322] ; USA [323] , [324] , [325] , [326] , [327] , [328] ; 44 countries [329] ; 53 countries [330] ; 56 countries [331] ; 142 countries [332] ; 149 countries [333] Effects on behaviors China [334] ; China, Italy [335] ; Denmark, Sweden [336] ; Germany [337] USA [338] , [339] , [340] , [341] ; 20 countries [342] ; 67 countries [343] Effects on medical practice Italy [344] ; Netherlands [345] ; UK [346] …”
Section: Quantifying the Effects On Npismentioning
confidence: 99%
“…Finally, Ref. [345] studies the effect of NPIs in a long term care institution in the Netherlands specialized on intellectual disabilities. The authors focused on incidents reported during the emergency respect to historical data.…”
Section: Quantifying the Effects On Npismentioning
confidence: 99%
“…There has only been limited research into the impact of COVID‐19 on social care staff and on behaviours that challenge. In terms of the latter, one study in the Netherlands found that, after an initial drop in reporting of incidents of aggression at the start of COVID‐19 restrictions, levels increased significantly (Schuengel et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In a study from the Netherlands, metadata on weekly incident and near-incident reports from 2016 to June 2020 involving over 14,000 clients with mild to serious intellectual disability in a long-term care organisation for people with intellectual disability were subjected to interrupted time series analysis, comparing the COVID-19 period with the pre-COVID-19 period [ 9 ]. The results showed that the measures taken against COVID-19 coincided with changes in weekly incident reports and drops in incident reports were observed immediately after these measures were announced and implemented, along with an unexpected drop in medication error reports, suggesting a lower rate of incident reporting.…”
Section: Discussionmentioning
confidence: 99%